UNDERSTANDING ALIEN LIMB SYNDROME: AN INTERDISCIPLINARY REVIEW OF NEURAL MECHANISMS AND CLINICAL FEATURES - Natalia Bębenek; Gabriela Barszcz; Monika Błądek; Karolina Drygała; Sylwia Wit; Paulina Frączkiewicz; Izabela Harpula; Radosław Ramotowski; Justyna Bogdan; Benedykt Baljon; Patryk Brzezicki (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Alien limb syndrome (ALS) can be described as complex, autonomous limb movements that occur against the patient’s will. The aim of this study is to summarise the current state of knowledge about alien limb syndrome. Methods: Literature in English was reviewed via PubMed and Google Scholar. After analyzing the abstracts, 30 publications closely related to the topic, 77% of them published between 2017 and 2024, were selected. Key findings: The etiology of alien limb syndrome remains poorly understood. There are several phenotypes of ALS associated with different sites of damage to brain structures: the frontal and callosal phenotypes, which may also be called anterior, and the posterior phenotype. Possible symptoms include: inter-manual conflict, mirror movements, grasping, utilization behaviour, hemineglect, hemianesthesia, ataxia. Alien limb syndrome usually occurs in association with damage to brain structures caused by tumors, vascular events or postoperative injuries and in people with corticobasal syndrome, Creutzfeldt-Jakob disease or Alzheimer’s disease. No specific therapeutic regimen has yet been identified. Sometimes behavioral therapy has been effective in patients and some use pharmacological treatment, including botulinum toxin. Conclusions: Alien limb syndrome is a relatively rare phenomenon. It is not a fully understood disease entity. Further research is needed to better determine the etiological factors and thus develop an appropriate therapeutic approach and be able to better care for patients.